2011
DOI: 10.1007/s00442-011-2038-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic properties of fronds from palms of varying height and habitat

Abstract: Because palms grow in highly varying climates and reach considerable heights, they present a unique opportunity to evaluate how environment and plant size impact hydraulic function. We studied hydraulic properties of petioles from palms of varying height from three species: Iriartea deltoidea, a tropical rainforest species; Mauritia flexuosa, a tropical rainforest, swamp species; and Washingtonia robusta, a subtropical species. We measured leaf areas, petiole cross-sectional areas, specific conductivity (K(S))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…With vessels in their trunks around 240 m in diameter, I. deltoidea also has some of the largest mean trunk vessel diameters when compared with several reported mature tropical species and growth forms (Ewers et al 1990, McCulloh et al 2011. Vessel sizes in the petioles were also found to increase (from 80 to 120 m in diameter) in larger, taller I. deltoidea palms (Renninger and Phillips 2011) and are among the largest of the measured vessel diameters in the branches of early-and late-successional trees (McCulloh et al 2011).…”
Section: Discussionmentioning
confidence: 76%
“…With vessels in their trunks around 240 m in diameter, I. deltoidea also has some of the largest mean trunk vessel diameters when compared with several reported mature tropical species and growth forms (Ewers et al 1990, McCulloh et al 2011. Vessel sizes in the petioles were also found to increase (from 80 to 120 m in diameter) in larger, taller I. deltoidea palms (Renninger and Phillips 2011) and are among the largest of the measured vessel diameters in the branches of early-and late-successional trees (McCulloh et al 2011).…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, recent studies (Renninger and Phillips, 2011) have shown that parts of the vasculature of the Washingtonia robusta palm are not functional (i.e., water conducting) at all times. As this may well be the case for other arborescent monocotyledons such as the studied Dracaena species, the complex network and interconnection of the vascular bundles within the ramification may compensate for this deficiency and allow for the adequate distribution of water and nutrients within the branch.…”
Section: Discussionmentioning
confidence: 95%
“…In palms, embolism occurs in petioles rather than in the stem (Sperry, , ; Renninger & Phillips, ; Renninger, McCulloh & Phillips, ). Our results are in accordance with the fact that small vessels are encountered in dry conditions because they are more resistant to cavitation (Hacke et al ., ) and are more easily refilled (Zimmermann, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with the fact that small vessels are encountered in dry conditions because they are more resistant to cavitation (Hacke et al ., ) and are more easily refilled (Zimmermann, ). Accordingly, Renninger & Phillips () specified (p. 933) that, ‘a monocot species with little ability for secondary growth would be especially resistant to embolisms in order to preserve its conductive tissue’, and concluded (p. 934) that, ‘opposing patterns were seen between metaxylem vessel diameter and vascular bundle densities in the tropical rainforest Iriartea deltoidea and the subtropical Washingtonia robusta . In I. deltoidea , taller palms had larger but less frequent vessels, while in W. robusta , taller palms had smaller but more frequent vessels in petioles’.…”
Section: Discussionmentioning
confidence: 99%